Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome secondary to antituberculosis drugs and associated with human herpes virus-7 (HHV-7). (31st July 2013) - Draz, Nehal; Datta, Sumona; Webster, Daniel P; Cropley, Ian
Abstract : Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a serious reaction to drugs with a clinical presentation of rash, fever, lymph node enlargement and internal organ involvement. Reports have described the reactivation of human herpes virus 6 (HHV-6) and other HHVs in association with this syndrome. We report a 41-year-old woman who developed a rash, fever, liver dysfunction, eosinophilia and atypical monocytosis 21 days after initiation of the quadruple therapy for tuberculous cervical lymphadnitis. HHV-7 DNA was detected in blood by PCR suggesting infection with or more likely reactivation of HHV-7 as a contributing factor or consequence of this serious adverse drug reaction.